A new species of the Australian genus Clinopsocus New from coastal California (Psocodea: ‘Psocoptera’: Elipsocidae) - Mockford, Edward L. (Zootaxa, 2018)
Clinopsocus nigrescens n. sp. is described from a series of adult females taken on boards stored in a garage in San Leandro, Alameda County, California. Clinopsocus is known from two other species, both Australian. The new species is highly neotenic and probably parthenogenetic.